2010
DOI: 10.1038/nn.2552
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced opening of TRPV1 ion channel is stabilized by the pore domain

Abstract: Summary TRPV1 is the founding and best-studied member of the family of temperature-activated transient receptor potential ion channels (thermoTRPs). Voltage, chemicals, and heat amongst other agonists allosterically gate TRPV1. Molecular determinants for TRPV1 activation by capsaicin, allicin, acid, ammonia, and voltage have been identified. However, the structures and mechanisms mediating its pronounced temperature-sensitivity remain unclear. Recent studies of the related channel TRPV3 identified residues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
230
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(248 citation statements)
references
References 42 publications
18
230
0
Order By: Relevance
“…In support of the hypothesis, single-channel and macroscopic kinetic analyses reveal that temperature changes only influence specific gating components (4,7,11). Although membrane lipids are prone to temperature-dependent phase transitions, both TRPV1 and TRPM8 remain activated by temperature following perturbations of membrane fluidity by either cholesterol changes (4) or lipid bilayer reconstitution (8).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In support of the hypothesis, single-channel and macroscopic kinetic analyses reveal that temperature changes only influence specific gating components (4,7,11). Although membrane lipids are prone to temperature-dependent phase transitions, both TRPV1 and TRPM8 remain activated by temperature following perturbations of membrane fluidity by either cholesterol changes (4) or lipid bilayer reconstitution (8).…”
mentioning
confidence: 68%
“…TRP channels have a membrane topology similar to voltage-gated K þ channels (12), albeit with relatively large intracellular termini (13). Both the pore domain (11,14,15) and the C terminus (16, 17) have been implicated in temperature gating. For example, single residue mutations at the outer pore of TRPV3 abrogated its heat activation (14), whereas alterations of the pore turret compromised the gating of TRPV1 (15).…”
mentioning
confidence: 99%
“…For example, swapping C-terminal domains between rat TRPV1 and TRPM8 channels has been reported to switch heat and cold sensitivity (27,28). Deletions within the TRPV1 C terminus have been shown to alter thermal threshold (29), and substitutions or point mutations within the turret or outer pore domain of TRPV1 have been shown to alter heat sensitivity (30,31). Recently, the linker region of TRPV1 connecting the pore-forming transmembrane core to the AR-containing N terminus has been suggested to specify heat sensitivity of the channel (32).…”
mentioning
confidence: 99%
“…Studies in TRPV1 showed that heat sensitivity can be altered by mutations in virtually any channel domain (33,(40)(41)(42)(43)(44)(45)(46), supporting the idea that molecular determinants of the hypothetical heat-sensing module are not localized in a single topologically defined channel element, but are instead distributed throughout the molecule (35). Although a full-length structure of TRPV1 is currently unavailable, the recent cryo-EM structure of TRPA1 revealed tight interations between the N-and C-termini (47), suggesting that topologically distant domains could be functionally coupled, in which case mutations that affect heat sensing or coupling mechanisms could be functionally indistinguishable.…”
Section: Discussionmentioning
confidence: 99%